An Overview of the Therapeutic Potential of Dimeric Flavonoids for Targeting Cancer Hallmarks - Inês Lopes; Isabel Meireles; Rafaela Rocha; Rui Medeiros; Fátima Cerqueira (BioChem)
Evidence found in the literature indicates that dimeric flavonoids constitute important therapeutic options against cancer. Using these molecules to prevent cancer progression might be a novel and promising therapeutic approach with advantages like fewer side effects, easy access in nature, overall health benefits and overcoming drug resistance. Cancer is a complex disease and still not understood, but there are some common mechanisms and biological characteristics underlying tumor progression that have been scrutinized over the years. This information was summarized in a conceptual framework designated as hallmarks of cancer. Dimeric flavonoids exert biological effects in several pathways involved in cancer hallmarks including cell growth, cell cycle, apoptosis, metastasis and metabolism.